2013
DOI: 10.1097/ta.0b013e31827e20e0
|View full text |Cite
|
Sign up to set email alerts
|

TEG-guided resuscitation is superior to standardized MTP resuscitation in massively transfused penetrating trauma patients

Abstract: Therapeutic study, level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
126
1
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(133 citation statements)
references
References 37 publications
2
126
1
4
Order By: Relevance
“…Thereafter, interests developed for using viscoelastic test guided transfusion algorithms in cardiovascular surgery and trauma [17]. Tapia et al demonstrated that TEG-guided resuscitation was superior to standard MTP in patients with penetrating injury that received more than 10 units of blood [14]. The study by Tauber et al further adds to the evidence that rotational thromboelastometry assays are useful in managing trauma patients [18].…”
Section: Discussionmentioning
confidence: 74%
“…Thereafter, interests developed for using viscoelastic test guided transfusion algorithms in cardiovascular surgery and trauma [17]. Tapia et al demonstrated that TEG-guided resuscitation was superior to standard MTP in patients with penetrating injury that received more than 10 units of blood [14]. The study by Tauber et al further adds to the evidence that rotational thromboelastometry assays are useful in managing trauma patients [18].…”
Section: Discussionmentioning
confidence: 74%
“…It has been extensively used in hepatic and cardiac surgery to guide resuscitation and has been shown in blunt trauma to be associated with specifi c transfusion requirements [ 85 ]. Tapia et al compared TEG directed resuscitation with MTP resuscitation in patients receiving massive transfusions as they are coagulopathic and even with aggressive resuscitation only 65 % of coagulation factor activity is delivered [ 86 ]. TEG directed therapy was found to be superior to MTP in both blunt and penetrating injury.…”
Section: Laboratory Assessment Of Coagulopathy During Mtmentioning
confidence: 98%
“…Bedside thromboelastography (TEG) is being used increasingly during damage control resuscitation to titrate blood component transfusion with favorable results [115]. Previously it was thought that fibrinolysis is unlikely after trauma.…”
Section: Damage Control Resuscitationmentioning
confidence: 99%